Repatriating a lost name: notes on McClelland and Griffith’s Cobitis boutanensis (Cypriniformes: Nemacheilidae) - Thoni, Ryan J.; Hart, Robbie (Zootaxa, 2015)
In 1842, a loach was described with great brevity in McClelland’s “On the freshwater fishes collected by William Griffith during his travels from 1835 to 1842” (McClelland 1842). The species was named Cobitis boutanensis McClelland and Griffith 1842, presumably after the country where it was collected. At that time, there was not a consensus on the spelling of ‘Bhutan’, which appeared commonly as ‘Bhotan’, ‘Bootan’, or ‘Boutan’. The locality of Cobitis boutanensis was described simply as “Boutan, on the Mishmee Mountains” (McClelland 1842). Hora (1928) subsequently amended the locality of the specimen to ‘Bolan Pass’ in what was then Afghanistan (now Pakistan). This amendment was based on the assumption that there was likely an error in spelling or interpreting the text in McClelland (1842). As a result, Cobitis boutanensis, now Paracobitis boutanensis in Eschmeyer (2015), has been referred to as a species endemic to Afghanistan for nearly 90 years.